2022
DOI: 10.1002/erv.2934
|View full text |Cite
|
Sign up to set email alerts
|

Association of gut‐specific non‐inflammatory T lymphocytes with chronic anorexia nervosa and constitutional thinness

Abstract: Objective Previous studies of AN showed low‐grade inflammation. Are low‐grade inflammation and circulating lymphocytes associated with chronic conditions? Method Peripheric blood cytokines were measured using Luminex™ technology in a chronic AN cohort (mean = 67.42 months), compared to Constitutional Thinness (CT), Constitutional Obesity (CO), and Healthy Controls (HC). Secondarily a prospective cohort of chronic AN (mean = 54.11 months) was recruited to compare the functional lymphocyte profile in blood by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Out of the 36 recruitment processes , only one 45 succeeded to have the minimal grade (8/10acceptable) for all of the 8 parameters considered, with only one other [39][40][41][42][43][44] that reached 7 out of these 8 parameters (Figure 1). When calculating a global quality score, it appeared that only 6 recruitment processes 22,23,[37][38][39][40][41][42][43][44][45] reached at least the global mark of 80%. Figure 1 also shows that the 'metabolicrelated biasing criteria' has been less considered by studies than the 'main clinical criteria'.…”
Section: Quality Assessment Of Recruitment Strategies In Previous Stu...mentioning
confidence: 99%
See 3 more Smart Citations
“…Out of the 36 recruitment processes , only one 45 succeeded to have the minimal grade (8/10acceptable) for all of the 8 parameters considered, with only one other [39][40][41][42][43][44] that reached 7 out of these 8 parameters (Figure 1). When calculating a global quality score, it appeared that only 6 recruitment processes 22,23,[37][38][39][40][41][42][43][44][45] reached at least the global mark of 80%. Figure 1 also shows that the 'metabolicrelated biasing criteria' has been less considered by studies than the 'main clinical criteria'.…”
Section: Quality Assessment Of Recruitment Strategies In Previous Stu...mentioning
confidence: 99%
“…The studies presented in the Figure 1 have been identi ed by an update (last bibliographic research run in February 2023) of the systematic reviews of the literature in CT completed in 2020 and 2021 48,49 (for further details in the research strategies, see these references 48,49 ). From these previous works, 4 new studies have been identi ed 26,[42][43][44] . In the present work, we refer to 'recruitment processes' instead of 'studies' as a single recruitment process sometimes led to several studies 13,14,18,19,39,40,43,44 (Figure 1).…”
Section: Quality Assessment Of Recruitment Strategies In Previous Stu...mentioning
confidence: 99%
See 2 more Smart Citations
“…The studies presented in the Figure 1 have been identified by an update (last bibliographic research run in February 2023) of the systematic reviews of the literature in CT completed in 2020 and 2021 48,49 (for further details in the research strategies, see these references 48,49 ). From these previous works, 4 new studies have been identified 26,[42][43][44] . In the present work, we refer to 'recruitment processes' instead of 'studies' as a single recruitment process sometimes led to several studies 13,14,18,19,39,40,43,44 (Figure 1).…”
Section: Quality Assessment Of Recruitment Strategies In Previous Stu...mentioning
confidence: 99%